2009
DOI: 10.1111/j.1467-8535.2008.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia learning and individual differences: Mediating the effects of working memory capacity with segmentation

Abstract: Research in multimedia learning lacks an emphasis on individual difference variables, such as working memory capacity (WMC). The effects of WMC and the segmentation of multimedia instruction were examined by assessing the recall and application of low (n = 66) and high (n = 67) working memory capacity students randomly assigned to either a segmented instruction (SI) or non-segmented instruction (NSI) version of a multimedia tutorial on historical inquiry. WMC was found to have a significant, positive effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 41 publications
5
52
0
Order By: Relevance
“…Exceptions can be found in work by van Gerven et al (2002van Gerven et al ( , 2004, who used a computation span test to control for working memory capacity between experimental groups. Another recent example is a study by Lusk et al (2009), who measured participants' individual working memory capacity with the OSPAN test and assessed the effects of segmentation of multimedia material in relation to working memory capacity. They found that students with high working memory capacity recalled more than students with low working memory capacity and generated more valid interpretations of the material presented.…”
Section: Individual Differencesmentioning
confidence: 99%
“…Exceptions can be found in work by van Gerven et al (2002van Gerven et al ( , 2004, who used a computation span test to control for working memory capacity between experimental groups. Another recent example is a study by Lusk et al (2009), who measured participants' individual working memory capacity with the OSPAN test and assessed the effects of segmentation of multimedia material in relation to working memory capacity. They found that students with high working memory capacity recalled more than students with low working memory capacity and generated more valid interpretations of the material presented.…”
Section: Individual Differencesmentioning
confidence: 99%
“…This worked-example effect is typically explained in terms of learners having the opportunity to develop meaningful schemas without having unnecessary demands placed on their cognitive processing. Other research has shown that learning can benefit from manipulations such as removing irrelevant, distracting content (e.g., Garner et al, 1989), using cues to direct attention to relevant content (e.g., Lorch, 1989;Mautone & Mayer, 2001), allowing learners to pace their own training in order allow sufficient processing time (e.g., Lusk et al, 2009;Mayer & Chandler, 2001), and "pretraining" students on relevant subcomponents of a system prior to the complete training phase (e.g., Mayer, Mathias, & Wetzell, 2002;Pollock, Chandler, & Sweller, 2002).…”
Section: Cognitive Load and Task Difficultymentioning
confidence: 99%
“…For example, Lusk and colleagues (Lusk, Evans, Jeffrey, Palmer, Wikstrom, & Doolittle, 2009) studied the effects of segmenting multimedia presentations, allowing learners to pace their own training instead of watching a video. Working memory capacity was assessed with the Operation Span test.…”
Section: Introductionmentioning
confidence: 99%